PENGARUH PRESTASI KERJA, SENIORITAS, DAN LOYALITAS TERHADAP PROMOSI JABATAN PADA DISCOVERY KARTIKA PLAZA HOTEL BALI - Mandiangan, Eliana Febisica; Rahyuda, Agoes Ganesha (E-Jurnal Manajemen, 2015)
Discovery Kartika Plaza Hotel is engaged in the business of tourism hospitality accommodation. This study aims to determine the effect of performance, seniority, and loyalty on job promotion at Discovery Kartika Plaza Hotel. Techniques used multiple linear regression analysis, the number of samples used is 70 people. These results indicate that performance has significant influence on the job promotion, seniority has significant influence on the job promotion, loyalty has significant influence on job promotion. Variable performance, seniority, and loyalty effect simultaneously significant effect on job promotion.
Keywords: promosi jabatan; prestasi kerja; senioritas; loyalitas